Factors Influencing Students Attitude and Motivation About Studying English as a Foreign Language - Reza Ayu Ningtiyas; Yeni Rahmawati* (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to analyze the factors that influence students' attitudes and motivation in learning English as a Foreign Language. These factors include various elements that influence students' desire and interest in learning English, such as internal and external motivation, perception of the usefulness of English, and previous language learning experience. The method to be used is quantitative research using descriptive design. The population is all students of the English Department at Universitas Muhammadiyah Kalimantan Timur (UMKT). The population of this study was about 196 students, and the researcher randomly selected a sample of 132 students from the total population for this study. Based on the results of the study, 69.7% of students have the motivation to learn English because they want to have a profession related to the language later. This shows that most students have a strong motivation to learn English because they see a direct relevance between English language skills and future career opportunities.